Impacts of a Post-Transport/Pre-Processing Rest Period on the Growth Performance and Serum Metabolites of Cattle Entering a Feedlot - P. L. Dahmer; Z. T. Buessing; N. B. Stafford; M. E. Reeb; C. A. Zumbaugh; A. J. Tarpoff; K. G. Odde; J. S. Drouillard; M. Theurer; T. Jones; C. K. Jones (Kansas Agricultural Experiment Station Research Reports, 2022)
Objective:The objective of this study was to evaluate the impact of a post-transport rest period on receiving calf growth performance and blood serum metabolites as indicators of immune function. Study Description:Eighty heifers were purchased from a sale barn and transported 6 hours to the Kansas State University Beef Cattle Research Center where they were processed at one of four times: immediately upon arrival or after a 6-, 24-, or 48-hour rest period. Cattle were then fed for 35 days with growth performance data collected weekly. Blood samples were also collected and analyzed for serum infectious bovine rhinotracheitis (IBR) titer and biochemical parameters. Results:Processing time did not impact (P>0.05) heifer average daily gain. Overall, dry matter intake (DMI) decreased linearly (P= 0.027) as the rest time increased. The number of days for heifers to reach a targeted DMI of 2.5% body weight was linearly increased (P= 0.023) as time of rest increased. Serum IBR titer for heifers processed at either 0 or 6 hours upon arrival was higher (P<0.01) on day 35 compared to day 0. This response was expected, as these cattle were vaccinated immediately or shortly after arrival. Interestingly, no difference in IBR titer was observed (P>0.05) between day 0 and day 35 for heifers processed at either 24 or 48 hours upon arrival, indicating potential seroconversion of IBR antibodies before vaccination. The Bottom Line:These results indicate that rest time after arrival and prior to processing may not affect calf growth performance, but there is evidence that a 6-hour rest period could maximize DMI upon arrival to a feedlot. Additional research with greater replication and more industry-standard experimental conditions should be conducted to further evaluate these parameters.
Keywords: anthelmintic efficacy; growth performance; receiving calf